PENGARUH PENGGUNAAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP KEAKTIFAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AQIDAH AKHLAK DI MADRASAH TSANAWIYAH TASIKMALAYA - Adistiani, Salma Sopia; Suryana, Nana; Munggaran, Nita Anjung (Prodi PAI IAILM Suryalaya, 2020)
This study aims to determine the influence of Contextual Teaching and Learning learning on the learning activeness of students in Aqidah Morals in MTs Puteran, Puteran Village, Pagerageung District, Tasikmalaya. The method used in this research is descriptive method with quantitative approach. To collect the data needed techniques such as questionnaires, interview guidelines and observation guidelines. Based on the results of data processing, it was found that Contextual Teaching and Learning in MTs Puteran was classified as sufficient (a score of 32,88 was obtained, above the classification of 31,74 to 36,11 with sufficient criteria). While the learning activeness of students in MTs Puteran is relatively low (obtained a value of 29,5, is on the interpretation scale between 25,75 to 30,5 with low criteria). And the effect of Contextual Teaching and Learning learning on the learning activeness of students in MTs Puteran has a positive and significant effect with sufficient categories, it is proven that rs = 0,57 is at an interval of 0,41 to 0,60 and tcount 3,26 ≥ ttable 1,72. Contextual Teaching and Learning determines the learning activeness of students by 32,49% while the remaining 67,51% is thought to be determined by other factors.